An Analysis of Language Learning Strategies at Eight Graders of Mts Plus Roudhotul Muhibbin Bekasi - Herni Suminar; Leroy Holman Siahaan; Franscy Franscy (Journal of Innovative and Creativity, 2025)
This study explores the dominant types of language learning strategies and their relationship to English learning outcomes among eighth-grade EFL (English as a Foreign Language) students at MTS Plus Roudhotul Muhibbin Bekasi. Language is a fundamental tool for communication, allowing humans to express their ideas and emotions. With the increasing importance of English in the global context, it is widely taught at various levels, from elementary school to university, and in informal educational settings. However, effective language learning requires the use of appropriate strategies. The study employs both qualitative and quantitative approaches using a descriptive case study method, involving 30 eighth-grade students at a private junior high school in Cibitung Bekasi. The research instruments include a set of questionnaires adapted from Oxford (1990), along with interviews, observations, and documentation. The findings reveal that students are not very aware of or proactive in using language learning strategies, as they rarely implement them in their studies. The analysis indicates that the most commonly used strategies among students are Cognitive (49%), Memory (18%), and Compensation (14%) strategies, followed by Metacognitive (12%), Affective (4%), and Social (3%) strategies. Additionally, methods such as translation and independent vocabulary learning are frequently used, reflecting the adaptation to the limited exposure to the target language in Indonesia. This study emphasizes the critical role of learning strategies in fostering students' independence and motivation in mastering English.